Impact of sleep disorders on behavioral issues in preschoolers with autism spectrum disorder - Distefano, Giacomo; Calderoni, Sara; Apicella, Fabio; Cosenza, Angela; Igliozzi, Roberta; Palermo, Giuseppina; Tancredi, Raffaella; Tritto, Giovanna; Craig, Francesco; Muratori, Filippo; Turi, Marco (Frontiers in Psychiatry, 2023)
Background Sleep disorders are one of the most common problems in children with Autism Spectrum Disorder (ASD). However, they often tend to be underdiagnosed and incorrectly treated in clinical practice. This study aims to identify sleep disorders in preschool children with ASD and to explore their relationship with the core symptoms of autism, the child’s developmental and cognitive level as well as the psychiatric comorbidities. Methods We recruited 163 preschool children with a diagnosis of ASD. The Children’s Sleep Habits Questionnaire (CSHQ) assessed sleep conditions. Multiple standardized tests were used to evaluate intellectual abilities, the presence of repetitive behaviors (through the Repetitive Behavior Scale-Revised), as well as the emotional-behavioral problems and the psychiatric comorbidities (through the Child Behavior Checklist -CBCL 11/2-5). Results The results showed that poor disorders had consistently higher scores in all areas assessed by the CSHQ and on the CBCL across all domains. The correlational analysis showed that severe sleep disorders were associated with higher scores in internalizing, externalizing, and total problems at the CBCL syndromic scales, and in all DSM-oriented CBCL subscales. Moreover, we found that the association between sleep disorders and restricted and repetitive behaviors (RRBs) is explained by the anxiety-related symptoms. Conclusion Based on these findings, the study recommends that screening for sleep problems followed by early intervention should constitute a routine part of clinical practice for children with ASD.